Melatonin treatment mitigates chilling injury in cold-stored guava fruit by regulating the metabolisms of reactive oxygen species and membrane lipid - Hongbin Chen; Yuzhao Lin; Qianying Zhuang; Xuanjing Jiang; Yazhen Chen; Yihui Chen; Hetong Lin (Postharvest Biology and Technology, 2026)

Revealing the synergistic mechanism of ionic strength and cassava starch-lauric acid complexes in driving the transition of myofibrillar protein emulsion to emulsion gel - Wenwen Hou; Xiuwen Lin; Linjing Gao; Hongbin Lin; Jiaxin Chen; Qian Liu (Food Chemistry, 2026)

Investigation of flavor formation mechanism of broad bean paste fermented by Bacillus amyloliquefaciens SCPC-RY2021 - Jiaying Cai; Ya Liu; Yue Xiang; Yilin Xie; Jie Tang; Chao Liu; Houqi Ning; Hongbin Lin (Food Research International, 2026)

Direct upcycling of Mn-rich residues into γ-MnOOH for efficient Alkaline OER - Wenting Jia; Lin Guo; Zhao Yu; Zhiqiang Li; Pengge Ning; Hongbin Cao (Journal of Environmental Management, 2026)

A membrane-mediated algal–bacterial coupling strategy for energy – efficient and low-carbon PHA production - Long Huang; Lin Liu; Guangyi Zhang; Guoqiang Li; Yingke Fang; Yuan Li; Huiying Yang; Hongbin Xu (Bioresource Technology, 2026)

Grass mulching optimizes microbial communities and enhances carbon nitrogen cycling in peach orchard soils across slope positions - Chengyi Huang; Caiyun Lu; Huijuan Huang; Hongbin Zhang; Liu Yang; Yian Chen; Lijin Lin; Kairui Zhang; Wenjie Liu; Dan Zhu; Hongping Li; Shou Yan (Nutrient Cycling in Agroecosystems, 2026)

Global-to-regional variations in the effects of grassland management on soil carbon - Xi Lin; Shengwei Zhang; Alfredo Huete; Han Y.H. Chen; Hongbin Zhao; Qinsi He; Shengwei Lv; Qian Zhang; Xiaoduo Zhang; Xiaofeng Zhang (Agriculture, Ecosystems & Environment, 2026)

Effect of protein–polyphenol interactions on the structural and digestive properties of pork myofibrillar proteins - Yu Chen; Qingyao Jiang; Yan Lu; Qiao Zeng; Ping Liu; Jiaxin Chen; Hongbin Lin; Jie Tang; Jie Zhao (Journal of Food Engineering, 2026)

Multi-omics reveals efficient thiamethoxam biodegradation but altered flavor profile by native microbiota during Pixian broad bean paste fermentation - Xuan Yu; Siqi Huang; Jie Tang; Chuanning Peng; Qi Wen; Siqi Chen; Lanqi lei; Chenxi Yang; Yuanxi Liu; Wenliang Xiang; Qing Zhang; Hongbin Lin; et al. (International Journal of Food Microbiology, 2026)

Unlocking the potential of umami peptides: A comprehensive review of preparation methods, evaluation strategies, health benefits, and taste transduction mechanisms - Jianhua Zhao; Xinyu Li; Lunjie Huang; Hongbin Lin; Qiang He (Food Research International, 2026)

Unveiling the metabolic mechanism of pesticide in food fermentation through metagenomics and metabolomics: A case study of β-cypermethrin in Pixian broad-bean paste - Siqi Huang; Xuan Yu; Jie Tang; Chuanning Peng; Qi Wen; Siqi Chen; Lanqi lei; Chenxi Yang; Yuanxi Liu; Wenliang Xiang; Qing Zhang; Hongbin Lin; et al. (Food Chemistry, 2026)

Revealing the polyphenol modulation mechanism for in vitro gastric digestion properties of myofibrillar proteins via noncovalent interaction - Yan Lu; Chaoqun Chen; Yu Chen; Shuaiqian Wang; Yanping Hu; Ping Liu; Hongbin Lin; Jie Tang; Jie Zhao (Food Chemistry, 2025)

Dual identification optical sensor for sodium benzoate and potassium sorbate based on UV-DAS combined with SEP-CNN-TL - Junfeng Wang; Rui Zhu; Jie Gao; Fei Xie; Mu Li; Changyin Li; Yungang Zhang; Hongbin Lin (Food Control, 2025)

Underlying mechanism of sucrose esters on myofibrillar protein O/W emulsion gel behaviour under different ionic strengths: Focus on emulsion characterisation, protein structural changes and molecular interactions - Xiang Li; Bo Wang; Wenwen Hou; Jie Tang; Hongbin Lin; Junqiang Lian; Qian Liu; Mingfeng Xu; Yuan Ma; Dong Yu; Dong Zhang; Jiaxin Chen (Food Chemistry, 2025)

DNP and ATP regulate disease progression in Neopestalotiopsis clavispora-infected guava fruit by modulating respiratory and energy metabolism - Hongbin Chen; Yifei Chen; Xuanjing Jiang; Yuzhao Lin; Yazhen Chen; Meiling Li; Yihui Chen (Postharvest Biology and Technology, 2025)

Catalytic selective production of mono-aromatics from low-density polyethylene via HNO3-induced surface oxidation of activated carbon - Xiaona Lin; Xiaojie Zhuansun; Zhen Sun; Hongtao Li; Hongbin Cong (Journal of Environmental Chemical Engineering, 2025)

Exercise Training Promotes Neural Remodeling and Vascular Regeneration in Cerebral Ischemic Rats Through the JNK/c-jun Signaling Pathway - Zijun Zhao; Xiuyun Chen; Zezhong Zhuang; Jianmin Chen; Zhijian Zheng; Wenwen Wu; Zhiyun Wu; Qiang Lin; Manli Chen; Ji Liu; Nan Liu; Ronghua Chen; et al. (Molecular Neurobiology, 2025)

Observational Study of Local and Non-local Effects on Aerosols Vertical Distribution in the Boundary Layers - Haijiong Sun; Lin Wang; Hongrong Shi; Liang Ran; Jinqiang Zhang; Zhixuan Bai; Bai Liu; Xiaoqiong Zhen; Xuehua Fan; Hongbin Chen (Aerosol Science and Engineering, 2025)

Using speleothem 87Sr/86Sr variations tracking the controls on trace element (Sr-Mg) compositions - Rishui Chen; Shuyu Xue; Hongbin Zhang; Michael Griffiths; Yi Zhou; Xing Liu; Zhenli Zhu; Lin Chen; Wei Guo; Shitou Wu; Hai Cheng; Junhua Huang; et al. (Global and Planetary Change, 2025)

Denitrification dominates nitrate attenuation and nitrous oxide effluxes under water table fluctuations - Lin Zhang; Helin Wang; Xiaohan Liu; Hongbin Zhan; Uwe Schneidewind; Stefan Krause; Menggui Jin; Xing Liang; Yanfeng Liu; Ping Li (Journal of Hazardous Materials, 2025)

Microplastics magnify inhibitive effects of perfluorooctanoic acid on the marine microbial loop - Peichun Lin; Xiaokun Liu; Zuyuan Gao; Yelinzi Yuan; Hongbin Liu; Lingfeng Huang; Zhili He; Qinglu Zeng; Shanquan Wang (Environmental Research, 2025)

Investigation the antioxidant mechanisms of Capsaicinoids on myofibrillar protein based on multispectral and molecular docking - Jianhua Zhao; Chunyan Jiang; Meijuan Lei; Yilin Xie; Jie Zhao; Jiaxin Chen; Mingyuan Yang; Dan Xiang; Jie Tang; Hongbin Lin (Food Chemistry, 2025)

Influence of Electrode Size on the Fragmentation Process of Rocks with Different Heterogeneities under High-Voltage Pulses - Yong Zhao; Yi Liu; Hongbin Liao; Tianyu Wang; Siwei Liu; Fuchang Lin (Rock Mechanics and Rock Engineering, 2025)

Grassland irrigation and grazing prohibition have significantly affected vegetation and microbial diversity by changing soil temperature and moisture, evidences from a 6 years experiment of typical temperate grassland - Xi Lin; Hongbin Zhao; Shengwei Zhang; Qinsi He; Alfredo Huete; Lin Yang; Xiaoduo Zhang; Xiaofu Zhang; Qidi Zhang; Simeng Cai (Agriculture, Ecosystems & Environment, 2025)

A high-resolution multiproxy speleothem record of Eastern China hydroclimate variation during last glacial maximum - Shuyu Xue; Hongbin Zhang; Michael L. Griffiths; Chengfei He; Yitao Liu; Junhua Huang; Hai Cheng; Wei Guo; Shitou Wu; Jianzong Zhou; Youfeng Ning; Lin Chen; et al. (Quaternary Science Reviews, 2025)

Theoretical estimations of carbon geological storage capacities in the deep aquifer in Songliao Basin: Insights from spatial stochastic simulation - Zhijian Sun; Lin Zhang; Wanli Xue; Chong Zhang; Hongbin Zhan; Yanfeng Liu (Journal of Environmental Management, 2025)

Strengthening effect of the CFRP method on fire-damaged segments - Hongbin Chen; Yujing Jiang; Diyang Chen; Xuepeng Zhang; Peng Yan; Bin Wang; Qiwei Lin (Tunnelling and Underground Space Technology, 2024)

Carbon emissions and drivers across five urban agglomerations of China: Comparison between the 12th and 13th Five-Year Plan periods - Jingjing Si; Yongjian Li; Congyu Zhao; Hongbin Zhan; Shizhuang Zhang; Lin Zhang (Stochastic Environmental Research and Risk Assessment, 2024)

Corrigendum to “Identification and molecular mechanisms of novel antioxidant peptides from fermented broad bean paste: A combined in silico and in vitro study” [Food Chemistry 450 (2024) 139297/ FOCH_FOODCHEM-D-23-08808] - Hongbin Lin; Jianhua Zhao; Yuqing Xie; Jie Tang; Qin Wang; Jie Zhao; Min Xu; Ping Liu (Food Chemistry, 2024)

Identification and molecular mechanisms of novel antioxidant peptides from fermented broad bean paste: A combined in silico and in vitro study - Hongbin Lin; Jianhua Zhao; Yuqing Xie; Jie Tang; Qin Wang; Jie Zhao; Min Xu; Ping Liu (Food Chemistry, 2024)

Interaction of pepper numbing substances with myofibrillar proteins and numbness perception under thermal conditions: A structural mechanism analysis - Shuaiqian Wang; Yu Chen; Yan Lu; Diandian Jiang; Hongbin Lin; Zhenju Jiang; Jie Tang; Wei Dong; Jie Zhao (Food Chemistry, 2024)

Thermal preference prediction through infrared thermography technology: Recognizing adaptive behaviors - Hongbin Li; Yanchen Liu; Huijun Wu; Borong Lin; Leqi Lei; Junkang He (Building and Environment, 2024)

The novel angiotensin-I-converting enzyme inhibitory peptides from Scomber japonicus muscle protein hydrolysates: QSAR-based screening, molecular docking, kinetic and stability studies - Baobei Wang; Hui Zhang; Yuxi Wen; Wenwen Yuan; Hongbin Chen; Luan Lin; Fengxian Guo; Zong-Ping Zheng; Chao Zhao (Food Chemistry, 2024)

Research progress on remediation of heavy metal contaminated soil by electrokinetic-permeable reactive barrier - Zhenhao Yang; Jing Tang; Haopeng Feng; Xi Liu; Xiaojie Zhuang; Hongbin Wang; Yangfeng Wu; Yuyao Guo; Lin Tang (Chemical Engineering Journal, 2024)

High-temperature energy storage with a new tri-layers polymer composites via hybrid assembly engineering - Fei Wen; Hongbin Yuan; Mengquan Jiang; Pingan Yang; Jian Wang; Lin Zhang; Lili Li; Gaofeng Wang; Wenjun Li; Wei Wu; Zhonghui Shen; Shujun Zhang (Chemical Engineering Journal, 2024)

Investigation into the potential mechanism of Bacillus amyloliquefaciens in the fermentation of broad bean paste by metabolomics and transcriptomics - Hongbin Lin; Shiqi Liao; Zesu Zhou; Ziting Yan; Jianhua Zhao; Yue Xiang; Min Xu; Jie Zhao; Ping Liu; Wengwu Ding; Yu Rao; Jie Tang (Food Research International, 2024)

Photodegradation of oxytetracycline hydrochloride by Z-scheme g-C3N4 @MIL-101(Fe) heterojunction: Experimental optimization, mechanism evaluation and practical application - Hongbin He; Bolong Liang; Shumin Lin; Yan Chen; Xin Zhang; Shu-Xuan Liang (Journal of Environmental Chemical Engineering, 2024)

Response of air pollution to meteorological conditions and socioeconomic activities associated to the COVID-19 outbreak in the Yangtze River Economic Belt - Jingjing Si; Lin Zhang; Shizhuang Zhang; Yongjian Li; Zhixin Zhang; Ziqi He; Ying Chen; Hongbin Zhan (Atmospheric Environment, 2024)

Global response of different types of grasslands to precipitation and grazing, especially belowground biomass - Xi Lin; Hongbin Zhao; Shengwei Zhang; Vijay P. Singh; Ruishen Li; Meng Luo; Shuai Wang; Xingyu Zhao; Shengwei Lv; Xinghui Chen (Agriculture, Ecosystems & Environment, 2024)

Ammonium enrichment, nitrate attenuation and nitrous oxide production along groundwater flow paths: Carbon isotopic and DOM optical evidence - Lin Zhang; Zhixin Zhang; Xin Huang; Jingwei Zhang; Uwe Schneidewind; Stefan Krause; Menggui Jin; Xing Liang; Hongbin Zhan (Journal of Hydrology, 2024)

Revealing the formation mechanisms of key flavors in fermented broad bean paste - Yue Xiang; Binbin Zhou; Chunyan Jiang; Zhirui Tang; Ping Liu; Wenwu Ding; Hongbin Lin; Jie Tang (Food Research International, 2024)

Recent progress of particle electrode materials in three-dimensional electrode reactor: synthesis strategy and electrocatalytic applications - Siwen Li; Bo Jiang; Gen Liu; Chunyan Shi; Hongbin Yu; Yingzi Lin (Environmental Science and Pollution Research, 2024)

Influence of solar activity and large-scale climate phenomena on extreme precipitation events in the Yangtze River Economic Belt - Yi Wu; Lin Zhang; Zhixin Zhang; Jingyun Ling; Shiqi Yang; Jingjing Si; Hongbin Zhan; Wenling Chen (Stochastic Environmental Research and Risk Assessment, 2024)

Selective recovery of lithium from spent lithium-ion batteries via mild hydrothermal driven Lewis acid-base reaction in aqua solution - Weiguang Lv; Jin Zhang; Yunpeng Liu; Jiao Lin; Xiaohong Zheng; Wenyi Yan; Hongbin Cao; Yi Zhang; Zhi Sun (Resources, Conservation and Recycling, 2023)

Synergistic direct and indirect central unit fluoridation of non-fullerene acceptor enables high-efficiency organic solar cells - Jing Wang; Hongbin Chen; Chenxi Li; Yi Lin; Yang Yang; Zaifei Ma; Yan Lu (Chemical Engineering Journal, 2023)

Targeted Metabolomic Analysis of the Eye Tissue of Triple Transgenic Alzheimer’s Disease Mice at an Early Pathological Stage - Liming Shen; Xiaoxiao Tang; Huajie Zhang; Hongbin Zhuang; Jing Lin; Yuxi Zhao; Xukun Liu (Molecular Neurobiology, 2023)

Microplastic contamination in fish: Critical review and assessment of data quality - Xiaohui Lin; Aoife A. Gowen; Hongbin Pu; Jun-Li Xu (Food Control, 2023)

A Systematic Investigation of Complement and Coagulation-Related Protein in Autism Spectrum Disorder Using Multiple Reaction Monitoring Technology - Xueshan Cao; Xiaoxiao Tang; Chengyun Feng; Jing Lin; Huajie Zhang; Qiong Liu; Qihong Zheng; Hongbin Zhuang; Xukun Liu; Haiying Li; Naseer Ullah Khan; Liming Shen (Neuroscience Bulletin, 2023)

Diffusion kurtosis imaging tractography reveals disrupted white matter structural networks in children with obstructive sleep apnea syndrome - Yanhua Li; Hongwei Wen; Wenfeng Li; Yun Peng; Hongbin Li; Jun Tai; Tingting Ji; Lin Mei; Yue Liu (Brain Imaging and Behavior, 2023)

Dl-3-n-butylphthalide activates Nrf2, inhibits ferritinophagy, and protects MES23.5 dopaminergic neurons from ferroptosis - Ziying Ye; Chuna Li; Shuqiong Liu; Hongbin Liang; Jialiang Feng; Danyu Lin; Ying Chen; Sudan Peng; Lulu Bu; Enxiang Tao; Xiuna Jing; Yanran Liang (Chemico-Biological Interactions, 2023)

Study on the Mechanism of Arsenic-Induced Lung Injury Based on SWATH Proteomics Technology - Yi Wang; Jun Zhang; Xinglai Zhang; Huajie Zhang; Xueshan Cao; Ting Hu; Jing Lin; Xiaoxiao Tang; Xiaolu Chen; Yuxuan Jiang; Xi Yan; Hongbin Zhuang; et al. (Biological Trace Element Research, 2023)

HIV-1 subtype B Tat enhances NOTCH3 signaling in astrocytes to mediate oxidative stress, inflammatory response, and neuronal apoptosis - Lin Gao; Weixi Sun; Dongmei Zhang; Yanxing Shang; Li Li; Wenhua Tao; Lei Zhang; Hongbin Liu (Journal of NeuroVirology, 2023)

Influence of seasonal water-level fluctuations on depth-dependent microbial nitrogen transformation and greenhouse gas fluxes in the riparian zone - Lin Zhang; Yanfeng Liu; Menggui Jin; Xing Liang; Stefan Krause; Uwe Schneidewind; Yiming Li; Hongbin Zhan (Journal of Hydrology, 2023)

Tannic acid exerts antifungal activity in vitro and in vivo against Alternaria alternata causing postharvest rot on apple fruit - Haixia Wang; Lin Fu; Chunli Li; Xinlu Zhang; Kpadonou Essedolo Narcisse; Haishi Qi; Chuanyu Han; Xiangyu Wang; Hongbin Ma; Chunyu Zhu; Fangliang Zheng (Physiological and Molecular Plant Pathology, 2023)

A temporally relaxed theory of physically or chemically non-equilibrium solute transport in heterogeneous porous media - Ying-Fan Lin; Junqi Huang; Elliot J. Carr; Tung-Chou Hsieh; Hongbin Zhan; Hwa-Lung Yu (Journal of Hydrology, 2023)

Sulfamethazine degradation by sulfite through GAC@Ni/Fe Three-Dimensional (3D) particle electrode activation: Contribution of active substance and synergy - Siwen Li; Hongbin Yu; Yingzi Lin; Suiyi Zhu; Gen Liu; Chunyan Shi (Process Safety and Environmental Protection, 2023)

Egg-yolk-derived carbon dots@albumin bio-nanocomposite as multifunctional coating and its application in quality maintenance of fresh litchi fruit during storage - Xianjie Su; Hetong Lin; Bofei Fu; Shanshan Mei; Mengshi Lin; Hongbin Chen; Zongping Zheng; Hangyu Bo; Da-Peng Yang; Yifen Lin (Food Chemistry, 2023)

Microbial deposition and growth on polyamide reverse osmosis membrane surfaces: Mechanisms, impacts, and potential cures - Hongbin Li; Yongqiang Guo; Chao Liu; Yi Zhou; Xiaofeng Lin; Fei Gao (Desalination, 2023)

Sustainable preparation of lignocellulosic nanofibrils and cellulose nanopaper from poplar sawdust - Wei Liu; Shuya Zhang; Kun Liu; Hongbin Yang; Qingyi Lin; Ting Xu; Xueping Song; Haishun Du; Long Bai; Shuangquan Yao; Chuanling Si (Journal of Cleaner Production, 2023)

Study on the Contribution of Seaport to Urban Economy: An Empirical and Quantitative Analysis of Xiamen Port - Wei Liu; Yanbin Yang; Qiaoyun Luo; Xufeng Zeng; Chuxin Chen; Junfeng Zhu; Weishan Lin; Hongbin Chen; Weiwei Huo; Mengxiao He; Yuping Jin; Jiangyu Xu (Journal of Marine Science and Engineering, 2022)
Ports play a vital role in the development of cities. In order to study the contribution of seaports to the urban economy, this paper uses the input–output method and multiplier theory to calculate the direct, indirect, and ripple economic contribution of ports to cities. Then, this paper selects Xiamen Port as an example to calculate the economic contribution. Xiamen Port is a major port on the southeast coast of China and an important node of the 21st Century Maritime Silk Road. It can provide a reference for other port cities. A more detailed index system for evaluating the economic contribution is also constructed. Next, the time series ARIMA model is used to predict the cargo throughput and container throughput of Xiamen Port in the next four years. Finally, there are some suggestions put forward for the development of Xiamen Port. The results show the total economic contribution of Xiamen Port to the city accounted for 10.48% of the city’s GDP in 2017. Direct, indirect, and ripple economic contributions accounted for 2.84%, 2.13%, and 5.51%, respectively. The contribution of Xiamen Port to the city is in line with the growth pole theory, which not only allows for rapid growth in Xiamen Port itself but also drives the development of the entire region through the multiplier effect. The cargo throughput and container throughput of Xiamen Port will maintain continuous growth in the next four years. Therefore, the development of Xiamen Port should be accelerated to enhance its economic contribution to the city.

Probiotic Potential and Effects on Gut Microbiota Composition and Immunity of Indigenous Gut Lactobacilli in Apis cerana - Mingkui Lv; Sifan Wang; Huajuan Yin; Kun Dong; Yiqiu Liu; Hongbin Pan; Qiuye Lin; Zhenhui Cao (Probiotics and Antimicrobial Proteins, 2022)

Micro-/Meso-Scale Distinction and Horizontal Migration of Tintinnid (Ciliophora: Tintinnida) Assemblages in Three Regions Around the North Pacific Ocean - Meiping Feng; Shiquan Lin; Wuchang Zhang; Chunsheng Wang; Hongbin Liu; Shunyan Cheung; Haibo Li; Michael R. Stukel; John Paul Irving; Na Li (Frontiers in Marine Science, 2022)
We explored the relationships among different tintinnid populations on micro-, meso-, and basin-scales from three regions across the Pacific Ocean, including the Costa Rica Dome (CRD) in the Eastern Pacific Ocean, the Celebes Sea (CS), and the Tokara Strait (TS) in the Western Pacific Ocean. We quantified the species occurrence, vertical and biogeographic distribution patterns, and morphological parameters of tintinnid assemblages. A total of 46 tintinnid species were observed, with more than half (63.0%) in common among the three areas, accounting for 97.1% of the total abundances. The numerically abundant forms remained more or less the same set of species in the three areas. However, community structure analyses, in terms of species, lorica oral diameter (LOD) size classes, and genera, revealed clear distinctions among different regions, as well as among different water depths. A Lagrangian simulation of passive dispersal in ocean currents across the Pacific Ocean, supported the hypothesis that greater similarity between tintinnid populations in the CS and TS (relative to CRD), was related to ocean circulation linkages between the populations. A latitudinal decline of tintinnid species richness was observed, mainly as a result of a decline of redundant species and warm-water species in colder areas. These data provide information unique insight into population variability of microzooplankton communities on micro- to meso- and even large scales in the world oceans.

First report of black leaf mold by Cladosporium tenuissimum on Paulownia fortunei - Liu Yuelian; Zhong Feiteng; Lu Shili; Chen Jie; Lin Pinling; Lin Xiao; Jiang Hongbin; Zhang Xuhong (Journal of Plant Pathology, 2021)

New insights into the fine-scale history of western–eastern admixture of the northwestern Chinese population in the Hexi Corridor via genome-wide genetic legacy - Hongbin Yao; Mengge Wang; Xing Zou; Yingxiang Li; Xiaomin Yang; Ailin Li; Hui-Yuan Yeh; Peixin Wang; Zheng Wang; Jingya Bai; Jianxin Guo; Jinwen Chen; et al. (Molecular Genetics and Genomics, 2021)

Bone marrow-derived mesenchymal stem cells improve post-ischemia neurological function in rats via the PI3K/AKT/GSK-3β/CRMP-2 pathway - Xiaohui Lin; Hongbin Chen; Manli Chen; Ting Li; Yongxing Lai; Longzai Lin; Peiqiang Lin; Ji Liu; Yixian Zhang; Ronghua Chen; Houwei Du; Xinhong Jiang; et al. (Molecular and Cellular Biochemistry, 2021)

Development of a 100 MPa water–gas two-phase fluid pressurization device - Shengbin Li; Heping Li; Lin Chen; Hongbin Zhou (Acta Geochimica, 2021)

Development of in-situ Micro-Raman spectroscopy system for autoclave experimental apparatus - Lin Chen; Heping Li; Shengbin Li; Liping Xu; Sen Lin; Hongbin Zhou (Acta Geochimica, 2020)

Plastic pollution in croplands threatens long‐term food security - Dan Zhang; Ee Ling Ng; Wanli Hu; Hongyuan Wang; Pablo Galaviz; Hude Yang; Wentao Sun; Chongxiao Li; Xingwang Ma; Bin Fu; Peiyi Zhao; Fulin Zhang; et al. (Global Change Biology, 2020)
Plastic pollution is a global concern given its prevalence in aquatic and terrestrial ecosystems. Studies have been conducted on the distribution and impact of plastic pollution in marine ecosystems, but little is known on terrestrial ecosystems. Plastic mulch has been widely used to increase crop yields worldwide, yet the impact of plastic residues in cropland soils to soil health and crop production in the long term remained unclear. In this paper, using a global meta‐analysis, we found that the use of plastic mulch can indeed increase crop yields on average by 25%–42% in the immediate season due to the increase of soil temperature (+8%) and moisture (+17%). However, the unabated accumulation of film residues in the field negatively impacts its physicochemical properties linked to healthy soil and threatens food production in the long term. It has multiple negative impacts on plant growth including crop yield (at the mean rate of −3% for every additional 100 kg/ha of film residue), plant height (−2%) and root weight (−5%), and soil properties including soil water evaporation capacity (−2%), soil water infiltration rate (−8%), soil organic matter (−0.8%) and soil available phosphorus (−5%) based on meta‐regression. Using a nationwide field survey of China, the largest user of plastic mulch worldwide, we found that plastic residue accumulation in cropland soils has reached 550,800 tonnes, with an estimated 6%–10% reduction in cotton yield in some polluted sites based on current level of plastic residue content. Immediate actions should be taken to ensure the recovery of plastic film mulch and limit further increase in film residue loading to maintain the sustainability of these croplands.

In Vitro Evaluation of Probiotic Potential of Lactic Acid Bacteria Isolated from Yunnan De’ang Pickled Tea - Zhenhui Cao; Hongbin Pan; Shijun Li; Chongying Shi; Sifan Wang; Fuyi Wang; Pengfei Ye; Junjing Jia; Changrong Ge; Qiuye Lin; Zhiyong Zhao (Probiotics and Antimicrobial Proteins, 2019)

Applications of Raman spectroscopic techniques for quality and safety evaluation of milk: A review of recent developments - Huirong He; Da-Wen Sun; Hongbin Pu; Lijun Chen; Li Lin (Critical Reviews in Food Science and Nutrition, 2019)

Land surface phenology of Northeast China during 2000–2015: temporal changes and relationships with climate changes - Yue Zhang; Lin Li; Hongbin Wang; Yao Zhang; Naijia Wang; Junpeng Chen (Environmental Monitoring and Assessment, 2017)

The implications of serial correlation and time-lag effects for the impact study of climate change on vegetation dynamics – a case study with Hulunber meadow steppe, Inner Mongolia - Yong Lin; Xiaoping Xin; Hongbin Zhang; Xu Wang (International Journal of Remote Sensing, 2015)

APRIL depletion induces cell cycle arrest and apoptosis through blocking TGF-β1/ERK signaling pathway in human colorectal cancer cells - Feng Wang; Lin Chen; Hongbin Ni; Guihua Wang; Weifeng Ding; Hui Cong; Shaoqing Ju; Shumei Yang; Huimin Wang (Molecular and Cellular Biochemistry, 2013)

Estimating groundwater recharge beneath irrigated farmland using environmental tracers fluoride, chloride and sulfate - Dan Lin; Menggui Jin; Xing Liang; Hongbin Zhan (Hydrogeology Journal, 2013)

Toxicity of Trimethyltin and Dimethyltin in Rats and Mice - Xiaojiang Tang; Xin Wu; Amber M. Dubois; Gang Sui; Banghua Wu; Guanchao Lai; Zhihong Gong; Hongbin Gao; Shenglai Liu; Zhiyong Zhong; Zhongning Lin; James Olson; et al. (Bulletin of Environmental Contamination and Toxicology, 2013)

The distribution of chlorophyll a in the tropical eastern Indian Ocean in austral summer - Lisha Hong; Chunsheng Wang; Yadong Zhou; Mianrun Chen; Hongbin Liu; Zhongyang Lin; Xunshu Song (Acta Oceanologica Sinica, 2012)

Novel microRNAs in silkworm (Bombyx mori) - Yimei Cai; Xiaomin Yu; Qing Zhou; Caixia Yu; Haiyan Hu; Jiucheng Liu; Hongbin Lin; Jin Yang; Bing Zhang; Peng Cui; Songnian Hu; Jun Yu (Functional & Integrative Genomics, 2010)

Retrieval of aerosol optical properties over the Beijing area using POLDER/PARASOL satellite polarization measurements - Xuehua Fan; Hongbin Chen; Longfu Lin; Zhigang Han; Philippe Goloub (Advances in Atmospheric Sciences, 2009)

A scheme for estimating tropical cyclone intensity using AMSU-A data - Zhigang Yao; Longfu Lin; Hongbin Chen; Jianfang Fei (Advances in Atmospheric Sciences, 2008)

Fluxes of methane and nitrous oxide in water-saving rice production in north China - Christine Kreye; Klaus Dittert; Xunhua Zheng; Xu Zhang; Shan Lin; Hongbin Tao; Burkhard Sattelmacher (Nutrient Cycling in Agroecosystems, 2007)

Retrieving atmospheric temperature profiles from AMSU-A data with neural networks - Yao Zhigang; Chen Hongbin; Lin Longfu (Advances in Atmospheric Sciences, 2005)